Resource Blessing, Revenue Curse? : Domestic Revenue Effort in Resource-Rich Countries - Crivelli, Ernesto; Gupta, Sanjeev (Washington, D.C. : International Monetary Fund, 2014)
This paper uses a newly constructed revenue dataset of 35 resource-rich countries for the period 1992-2009 to analyze the impact of expanding resource revenues on different types of domestic (non resource) tax revenues. Overall, we find a statistically significant negative relationship between resource revenues and total domestic (non resource) revenues, including for the major tax components. For each additional percentage point of GDP in resource revenues, there is a reduction in domestic (non resource) revenues of about 0.3 percentage points of GDP. We find this primarily occurs through reduced effort on taxes on goods and services-in particular, the VAT- followed by a smaller negative impact on corporate income and trade taxes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet